1959
DOI: 10.1146/annurev.pp.10.060159.001425
|View full text |Cite
|
Sign up to set email alerts
|

The Macronutrient Elements

Abstract: The term "macronutrient" is recent, having come into popular usage since the general acceptance of the term "micronutrient." Therefore, the term "macronutrient element" suggests· one of the nine elements needed by plants in larger quantity, namely: nitrogen, phosphorus, sulfur, calcium, magnesium, potassium, carbon, hydrogen, and oxygen. However, only the first six which can be supplied conveniently as fertilizers are ordinarily con sidered among the macronutrients. In plant physiology, the understanding assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

1961
1961
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…The cation exchange capacity of roots is lower in corn than in soybean (Fernandes and Souza, 2006). Roots having a high charge density tend to accumulate bivalent ions in contrast to roots of low charge density differentially absorbing univalent ions (Wallace and Smith 1955 cited by Broyer and Stout, 1959). So, corn plants are less efficient than soybean plants in Ca 2+ uptake from soil solution and an increase in soil exchangeable Ca content followed by decreased level of exchangeable Mg with gypsum addition must have favored the Ca 2+ uptake by corn plants.…”
Section: Resultsmentioning
confidence: 99%
“…The cation exchange capacity of roots is lower in corn than in soybean (Fernandes and Souza, 2006). Roots having a high charge density tend to accumulate bivalent ions in contrast to roots of low charge density differentially absorbing univalent ions (Wallace and Smith 1955 cited by Broyer and Stout, 1959). So, corn plants are less efficient than soybean plants in Ca 2+ uptake from soil solution and an increase in soil exchangeable Ca content followed by decreased level of exchangeable Mg with gypsum addition must have favored the Ca 2+ uptake by corn plants.…”
Section: Resultsmentioning
confidence: 99%
“…Williams and Coleman (1950) found that the CECR was double in soybean as compared with corn. The roots possessing a high charge density tend to accumulate divalent ions in contrast to roots with a low charge density differentially absorbing univalent ions (Broyer and Stout, 1959). Therefore, corn and wheat plants are less efficient than soybean plants in Ca uptake from the soil solution.…”
Section: Resultsmentioning
confidence: 99%
“…Since K+ is required for carbamyl phosphate synthesis in extracts of Rana pipiens liver (Table IV, 29) , it seems logical to postulate that a defi ciency could limit or prevent the biosynthesis of arginine, citrulline, and pyrimidines in organisms where carbamylphosphate synthetase is operative. Potassium has been shown to be required for the enzymatic synthesis of S adenosylmethionine in yeast and animals (Table IV, [36][37][38][39] and, thus, could play a role in the metabolism of methyl transfer. Finally, there are several enzymes involved in the synthesis of vitamins, co factors, and coenzymes (Table IV, 42,21,30,31,43,24,45) that could affect protein synthesis in directly.…”
Section: N� + Inhibited 112 113mentioning
confidence: 99%